Analysis of Mechanical Power Flow in an Electric Drive Operating Under Vibration Conditions - Ermolaev, Artem; Plekhov, Aleksandr; Titov, Dmitriy; Chakirov, Roustiam; Vagapov, Yuriy (2018 X International Conference on Electrical Power Drive Systems (ICEPDS), 2018)
This paper discusses the analysis of mechanical power flow in an electric motor drive operating under variation of conditions. The drive system vibration generates the oscillation in the supplied active power which can reduce performance of the system and increase the actual load on the shaft. It is shown that the vibration damper installation significantly decreases the oscillations in mechanical power flow on the motor shaft and improves characteristics of the system operation. The paper provide analysis of two models of the electric drive installed on the platform - the system which is quipped with vibration dampers and without.